Translation and validation of the PACIC+ questionnaire: The Thai version - Daniel Zeugfang (2018)
© 2018 The Author(s). Background: The number of patients with chronic illness is increasing worldwide. These patients usually receive care from a primary care facility. The Patient Assessment of Chronic Illness Care (PACIC) is a tool that is increasingly used in several countries to measure how the patients perceive the care they receive. The goal of this validation study is to provide and validate an extended version of the tool, the PACIC+ questionnaire, in Thailand. Methods: In this observational validation study, patients with type 2 diabetes from the outpatient clinic at a university hospital in Thailand completed the PACIC+ at the clinic. For follow-up, they received the questionnaire per mail after four weeks. The Thai PACIC+ comprises 26 items, which map onto 5 subscales and a summary score related to the Chronic Care Model (CCM) and 5 subscales and a summary score related to the 5A model, a counseling model for behavioral changes. Data-analysis focused on the use of most extreme answering categories (> 15%), internal consistency (Cronbach's alpha), and test-retest reliability. An exploratory factor analysis (EFA) was performed for the CCM and the 5A model separately to examine the factor structure. Results: A total of 151 patients participated. The average age of the sample was 63 ± 9 years (range 29-86 years). Fifty-three percent of the respondents were female. In the Delivery System subscale, 20% of patients reported the highest possible value; in all other subscales, relative frequencies of the most extreme categories did not exceed 15%. Cronbach's alpha per subscale varied from 0.58 to 0.81, while that of the summary scores were 0.89 and 0.91. The mean difference from the test-retest varied from - 0.06 to 0.17 across subscales. The Kaiser-Meyer-Olkin criterion for sampling adequacy (KMO) was good for both models as well as the Bartlett's test for sphericity p. While the factor loadings in rotated factor solution showed good concordance with the CCM, concordance was not as good for the 5A model, especially for the subscales "Assess" and "Advice". Conclusion: A validated Thai version of the PACIC+ is now available to measure how the patients perceive the care they receive.